2016
DOI: 10.1371/journal.pone.0160442
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Diabetic Retinopathy – Could Endothelin 2 Be Part of the Answer?

Abstract: PurposeThe endothelins are a family of three highly conserved and homologous vasoactive peptides that are expressed across all organ systems. Endothelin (Edn) dysregulation has been implicated in a number of pathophysiologies, including diabetes and diabetes-related complications. Here we examined Edn2 and endothelin receptor B (Endrb) expression in retinae of diabetic mouse models and measured serum Edn2 to assess its biomarker potential.Materials and MethodsEdn2 and Ednrb mRNA and Edn2 protein expression wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Many studies have implicated Müller cells in neuroprotective pathways for photoreceptor survival (Bringmann et al, 2009;Goh et al, 2016). In particular, EDN2 is produced by photoreceptors in a wide variety of retinal injuries and early stage diseases, and it has been proposed as an early biomarker for diabetic retinopathy (Binz et al, 2016;Bramall et al, 2013;Braunger et al, 2013). When we checked for the presence of this molecule in Faim −/− retinas, we found that both EDN2 immunoreactivity and mRNA expression were increased at 2 months, implying that photoreceptors may have already been impaired by harmful stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have implicated Müller cells in neuroprotective pathways for photoreceptor survival (Bringmann et al, 2009;Goh et al, 2016). In particular, EDN2 is produced by photoreceptors in a wide variety of retinal injuries and early stage diseases, and it has been proposed as an early biomarker for diabetic retinopathy (Binz et al, 2016;Bramall et al, 2013;Braunger et al, 2013). When we checked for the presence of this molecule in Faim −/− retinas, we found that both EDN2 immunoreactivity and mRNA expression were increased at 2 months, implying that photoreceptors may have already been impaired by harmful stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Edn2 transcripts are known to be highly expressed during retinopathy of prematurity and diabetic retinopathy. [39][40][41] The induction of Edn2 transcripts has been reported in photoreceptors of diverse photoreceptor degeneration models. 42 In addition, in the acute light damage model, expression of endothelin receptor B (Ednrb) transcripts is increased in Müller glia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, crystallin B2, a family of crystallins that are known to have a role in the adaptive mechanisms taking place in the diabetic retina [ 78 ], is increased twofold in Ins2 Akita mice that received ASC-CM. Endothelin-2, a candidate biomarker for controlled vascular modulation [ 79 , 80 ], was significantly increased in Ins2 Akita mice that received saline with a twofold further increase in mice that received ASCs and ASC-CM. However, for any given gene, the relative differences in expression between Ins2 Akita mice that received ASCs versus ASC-CM was more profound at 3 weeks than at 3 days.…”
Section: Discussionmentioning
confidence: 99%